(untitled) (Razi Medical Journal, 2025)
Sentinel lymph node biopsy (SLNB) has become the gold standard for axillary staging in early-stage breast cancer, significantly reducing the morbidity associated with full axillary lymph node dissection. This study represents the first systematic evaluation of SLNB in a Libyan patient population, with integration of multimodal pathological assessment and hormonal profiling. Twenty women with histologically confirmed invasive breast carcinoma underwent SLNB at Alhelal and Alzuhor University Hospitals between 2023 and 2025. Intraoperative touch imprint cytology, hematoxylin and eosin staining, and pancytokeratin immunohistochemistry were performed to detect nodal metastasis. SLN metastasis was observed in four patients (20%), with macrometastases identified in three and micrometastasis in one case—detected only by immunohistochemistry. Hormonal receptor analysis showed heterogeneity, with strong ER/PR positivity in the micrometastatic case. These findings underscore the essential role of immunohistochemistry in nodal staging and align with regional and international data.